Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Our Q&A platform offers a seamless experience for finding reliable answers from experts in various disciplines. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

If g(x) = 4x - 3 and h(x) = -4x, what is g(5) + h(3)?

Sagot :

Answer:

g(5) + h(3) = 5

Step-by-step explanation:

g(5)

[tex]g(5) = 4(5) - 3\\\rule{150}{0.5}\\g(5) = 20 - 3\\\\\boxed{g(5)=17}[/tex]

h(3)

[tex]h(3) = -4(3)\\\rule{150}{0.5}\\\boxed{h(3) = -12}[/tex]

g(5) + h(3)

[tex]17 + -12\\\rule{150}{0.5}\\17 - 12\\\\\boxed{5}[/tex]

Hope this helps.